Optimal parity distribution – when is the best time to cull sows? - Dhuyvetter, Kevin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The economic impact of alternative sowculling strategies was examined by simulating costs and returns for a farrowing-to-weaning swine operation. Culling strategies considered were to sell sows after parity 1 (P1) through parity 10 (P10). These 10 culling strategies resulted in different parity distributions. The optimal parity distribution is a complex issue, because it is related to conception rates, litter size, feed intake, as well as other factors. Results of this analysis indicate that the most economical time to cull a sow is after her eighth or ninth parity. This results in a breeding herd comprised of 18 to 20% gilts and a herd average parity of 3.5 to 4.0. However, the additional benefits of keeping a sow beyond about six parities are relatively small. The optimal time to cull a sow decreases as the cost of replacement gilts increases and vice versa. Feed costs impact the level of costs and returns but have very little impact on the optimal parity distribution. Similarly, over a range of conception rates and litter sizes, the optimal time to cull a sow is relatively constant.
Keywords: Swine; Parity distribution; Culling; Farrowing-to-weaning; Economics